Pengaruh Struktur Modal, Risiko Bisnis dan Pertumbuhan Penjualan terhadap ROE Perusahaan Manufaktur - Dina Ika Kaptiana; Nadia Asandimitra (BISMA (Bisnis dan Manajemen), 2018)
This research was conducted to determine the effect of capital structure, business risk and sales growth with ROE for manufacturing companies (sector industry consumer goods) during 2008-2012. The independent variable is capital structure, business risk and sales growth.The sample was manufacturing (sector industry consumer goods),which publishes the annual report and quarterly financial reports I-IV during 2008-2012. It uses purposive sampling method. This data using secondary data obtained from the annual report and quarterly financial statements issued I-IV manufacturing companies (sector industry consumer goods) on the Stock Exchange. Analysis data method is using multiple linier regression. The analysis showed simoultantly variable capital structure, business risk and growth in sales affect ROE. Business risk get positive effect to ROE. While the capital structure and sales growth has no effect to ROE. Variable explaining independent variable is get 69,9% while the rest 30,1% can influenced by other variable.